2021
DOI: 10.3390/rs13214285
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Spatiotemporal Context Refinement Network for Precipitation Nowcasting

Abstract: Precipitation nowcasting by radar echo extrapolation using machine learning algorithms is a field worthy of further study, since rainfall prediction is essential in work and life. Current methods of predicting the radar echo images need further improvement in prediction accuracy as well as in presenting the predicted details of the radar echo images. In this paper, we propose a two-stage spatiotemporal context refinement network (2S-STRef) to predict future pixel-level radar echo maps (deterministic output) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The STConvS2S consists of only convolutional layers, and the authors showed that STConvS2S worked faster than PredRNN for the radar echo forecasting task. Niu et al (2021) proposed a two-stage spatiotemporal context refinement network (2S-STRef), which is two-fold as the name suggests. The first stage is a spatiotemporal prediction network that gives a first-stage prediction using a spatiotemporal RNN module incorporated into an encoder-decoder framework.…”
Section: D Rainfall Forecastingmentioning
confidence: 99%
“…The STConvS2S consists of only convolutional layers, and the authors showed that STConvS2S worked faster than PredRNN for the radar echo forecasting task. Niu et al (2021) proposed a two-stage spatiotemporal context refinement network (2S-STRef), which is two-fold as the name suggests. The first stage is a spatiotemporal prediction network that gives a first-stage prediction using a spatiotemporal RNN module incorporated into an encoder-decoder framework.…”
Section: D Rainfall Forecastingmentioning
confidence: 99%
“…In recent times, there has been a lot of interest directed toward this timeframe as a result of the commencement of the Subseasonal to Seasonal Prediction Experiment. The linked processes of the atmosphere and the ocean are essential for annual forecasting, and the occurrence of El Nino in the equatorial region of the Pacific Ocean is a classic example [9]. Many large datasets connected to this program include S2S projections from tactical and academic simulations, which are useful for possible ML requests.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods for radar echo extrapolation include cross-correlation methods [9,10], centroid tracking methods [11,12] and optical flow-based methods [13,14]. The cross-correlation methods calculate the correlation of each sub-region in two consecutive radar echo images to get the motion vectors [15]. These methods have low prediction accuracy regarding the condition that echoes evolve rapidly [16].…”
Section: Introductionmentioning
confidence: 99%